Evolution of resource use and property rights under risk: Issues - Swallow, B.M. (International Livestock Centre for Africa, 1994)
Since September 1993, ILCA and IFPRI have been engaged in a discussion about the most important, researchable, issues in the area of property rights. A concept note has been developed for collaborative research on the evolution of resource use and property institutions under risk. The starting point or framework was the Boserup, McIntire (and others) model of gradual intensification. This model has been used in documents such as the Winrock Assessment of Animal Agriculture to predict paths of future development and recommend research to facilitate that development. Basically, property rights systems follow the Demsetz model which says that population growth alters factor prices, driving up the value of land and giving rise to demand for individualization of property rights The model implies that the main role of research organizations is to develop land-saving technologies. However, the model ignores three important issues: (1) property rights systems have important risk management implications; (2) property rights systems have implications for the distribution of income and opportunity; and (3) property rights systems also entail different transactions costs. The path of intensification and agricultural development becomes ambiguous once these issues are considered. At least three alternative paths are possible. One, development may proceed along a path of gradual intensification. Two, the risk management and equity aspects of common property may block the process of intensification. Three, intensification may occur in a way that is socially Undesirable. It is important, therefore, to undertake research so that we can better understand the relationships between population growth, commercialization, risk, equity and transaction costs. The paper discusses these three omitted issues and listed researchable questions which arise from this discussion.